2013
DOI: 10.4103/0019-5413.108933
|View full text |Cite
|
Sign up to set email alerts
|

Ulnar buttress arthroplasty after enbloc resection of a giant cell tumor of the distal ulna

Abstract: Enbloc resection with or without ulnar stump stabilization is the recommended treatment for giant cell tumors (GCT) of the distal ulna. A few sporadic reports are available where authors have described various procedures to prevent ulnar stump instability and ulnar translation of carpal bones. We report a GCT of the distal ulna in a 43-year-old male which was resected enbloc. The distal radioulnar joint was reconstructed by fixing an iliac crest graft to the distal end of the radius (ulnar buttress arthroplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…4 To avoid the complications related to wrist instability and DRUJ after resection of GCT distal ulna, many procedures have been described in the literature. Harness and Mankin 2 recommended iliac bone graft as ulnar buttress which was also performed by Hashizume et al, 25 Naik et al, 26 and Tsai et al 27 Wurapa and Whipple 28 reconstructed the DRUJ with twostage allograft. Some authors have combined the ECU tenodesis with iliac crest graft to the distal radius.…”
Section: Discussionmentioning
confidence: 99%
“…4 To avoid the complications related to wrist instability and DRUJ after resection of GCT distal ulna, many procedures have been described in the literature. Harness and Mankin 2 recommended iliac bone graft as ulnar buttress which was also performed by Hashizume et al, 25 Naik et al, 26 and Tsai et al 27 Wurapa and Whipple 28 reconstructed the DRUJ with twostage allograft. Some authors have combined the ECU tenodesis with iliac crest graft to the distal radius.…”
Section: Discussionmentioning
confidence: 99%
“…Distal ulna resection is another option and it is performed when the tumor is not confined to the cortex, or in the case of a soft tissue component, a pathological fracture, or an unsuccessful previous surgery [ 11 ]. Darrach et al [ 12 ] reported that the distal ulna can be excised sacrificing function and indicated its excision for degenerative conditions.…”
Section: Discussionmentioning
confidence: 99%
“…These techniques reported pain relief in the majority of the patients but there was no evaluation upon weight loading of the hand [18] . Ulnar buttress arthroplasty with iliac crest autograft and ulnar stump stabilization is another reconstructive procedure and has reported good functional outcomes [20] . Following distal ulna excision, DRUJ prosthesis can be an option to reconstruct the joint.…”
Section: Discussionmentioning
confidence: 99%